Problems and Life Effects Experienced by Tinnitus Research Study Volunteers: An Exploratory Study Using the ICF Classification - Manchaiah, Vinaya; Beukes, Eldré W.; Granberg, Sarah; Durisala, Naresh; Baguley, David M.; Allen, Peter M.; Andersson, Gerhard (Journal of the American Academy of Audiology, 2018)
Tinnitus is one of the most distressing hearing-related symptoms. It is often associated with a range of physiological and psychological complications, such as depression, anxiety, and insomnia. Hence, approaching tinnitus from a biopsychological perspective may be more appropriate than from purely a biomedical model.The present study was aimed at determining the relationship between tinnitus and the problems and life effects experienced by UK-based tinnitus research study volunteers. Open-ended questions were used. Responses were classified using the International Classification of Functioning, Disability and Health (ICF) framework to understand the impact of tinnitus in a multidimensional manner using a biopsychosocial perspective.A cross-sectional survey design was used.Study sample included a sample of 240 adults with tinnitus who were interested in undertaking an Internet-based intervention for tinnitus.The data were collated using two open-ended questions. The first focused on problems related to having tinnitus and the second to life effects as a result of tinnitus. Responses were analyzed using a simplified content analysis approach to link concepts to ICF categories in accordance with established linking rules. A Wilcoxon signed-rank test was performed to compare the number of responses between the two questions.There were 764 responses related to problems identified, 797 responses associated with life effects due to tinnitus, and 37 responses that did not fit into any ICF category. No significant differences were observed in the number of responses between the two questions. In addition, no significant association between the number of responses reported and demographic variables was found. Most of the problems and life effects experienced by tinnitus sufferers were related to body function, followed by activity limitations, and participation restrictions. Only a few responses were related to environmental and personal factors. The most frequent responses related to body function involved “emotional functions” (b152), “sleep functions” (b134), “hearing functions” (b230), “sustaining attention” (b1400), and “energy level” (b1300). For activity limitations and participation restrictions they were “communicating with—receiving—spoken messages” (d310), “socialization” (d9205), “handling stress and other psychological demands” (d240), and “recreation and leisure” (d920). The most frequently occurring responses related to environmental factors were “sound intensity” (e2500), “sound quality” (e2501), and “general products and technology for communication” (e1250). “Coping styles” was the most frequently occurring personal factor.The study highlights the use of open-ended questions in gathering useful information about the impact of tinnitus. The responses coded to ICF show that tinnitus impacts many domains, not only particularly body function, but also activity limitations and participation restrictions. The results demonstrate the heterogeneous nature of the impact of tinnitus on people affected.
Keywords: activity limitations; body function; ICF; open-ended questions; participation restrictions; tinnitus